“True Is the Pole when He Gets Drunk”. On the Persistence of Romantic Sarmatism in a Contemporary Liquor Store - Wijas, Jędrzej (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
Drawing upon inspirations from anthropology of everyday, visual studies and analyses of Neo-Sarmatian issues, the article is devoted to the subject of vodka (and, in its broader context, also the motif of consuming strong alcohol) in Polish literature of the first half of the 19th century, especially in reference to works by Adam Mickiewicz and Juliusz Słowacki. The impulse for analysis was the appearance of vodkas whose names are connected with the figures and the oeuvre of both Romantic poets in the Polish alcohol market. Tracing their oeuvres with regard to the motif of vodka, the attitudes of the writers to alcohol, reconstructed on the basis of (auto)biographical documents, as well as analyzing visual and textual elements of the vodkas made it possible to pose a thesis concerning the durability of social influence of Romantic Sarmatism in commercial space.